Near-Field HF-RFID and CMA-Based Circularly Polarized Far-Field UHF-RFID Integrated Tag Antenna - Arnon Sakonkanapong; Chuwong Phongcharoenpanich (My University, 2020)
This research proposes an integrated high-frequency (HF) and ultrahigh-frequency (UHF) passive radio frequency identification (RFID) tag antenna for near-field (13.56 MHz) and far-field (920–925 MHz) communication. This tag antenna is advantageous for the applications with lossy material in the near-field communication and mitigates polarization loss in the far-field communications. The HF-RFID tag antenna is of square spiral structure, and the circularly polarized UHF-RFID structure consists of a square loop radiator with cascading loop feeding and shorted stub. The structure of HF-RFID tag antenna situated inside the circularly polarized UHF-RFID tag can avoid the significant effect of the near-field magnetic coupling from the square loop. The UHF-RFID tag antenna is realized by using characteristic mode analysis for wideband circular polarization. The HF-RFID structure is conjugate-matched with NXP NT3H2111 chip, and the UHF-RFID structure is conjugate-matched with NXP G2X chip. Simulations were carried out, and an antenna prototype was fabricated. The experimental results reveal that the radiation pattern of UHF-RFID tag antenna is bidirectional with a gain of 0.31 dBic. The impedance bandwidth covers the frequency range of 903–944 MHz, and the axial ratio in boresight direction at 922.5 MHz is 1.67 dB, with the axial ratio bandwidth over 863–938 MHz. The maximum near-field and far-field reading ranges are 4.9 cm and 8.7 m. The proposed integrated dual-band passive tag antenna is operationally ideal for HF-RFID and UHF-RFID applications.
Keywords: Axial ratio; Loop antenna; Antenna Design and Analysis